Bullous mastocytosis - Nayak Surajit; Acharjya Basanti; Devi Basanti; Behera Samira (Wolters Kluwer Medknow Publications, 2007)
Mastocytosis is a condition characterized by the disorderly infiltration of mast cells in several tissues and comprises many different clinical situations varying from indolent cutaneous forms to malignant and systemic conditions. Bullous mastocytosis is a rare variant of cutaneous mastocytosis manifested by the diffuse infiltration of skin by mast cells, where cutaneous bullae is the predominant feature. We present this case for its rarity and diversity.